Q: Which is longer 3 yds or 6 ft?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

55 ft * 12 ft * 18 ft = 55/3 yds * 4 yds * 6 yds = 440 cubic yards55 ft * 12 ft * 18 ft = 55/3 yds * 4 yds * 6 yds = 440 cubic yards55 ft * 12 ft * 18 ft = 55/3 yds * 4 yds * 6 yds = 440 cubic yards55 ft * 12 ft * 18 ft = 55/3 yds * 4 yds * 6 yds = 440 cubic yards

1 yd = 3 ft 2 yds = 6 ft 3 yds = 9 ft 4 yds = 12 ft . . . 10 yds = 30 ft

1 ft = 12 in ⇒ 6in = 6 ÷ 12 ft = 1/2 ft. 1 yd = 3 ft ⇒ 181/2 ft = 181/2 ÷ 3 yds = 61/6 yds

18 ft = 6 yds 12 ft = 4 yds 6 yds x 4 yds = 24 yds2

6 sq. yds

Related questions

55 ft * 12 ft * 18 ft = 55/3 yds * 4 yds * 6 yds = 440 cubic yards55 ft * 12 ft * 18 ft = 55/3 yds * 4 yds * 6 yds = 440 cubic yards55 ft * 12 ft * 18 ft = 55/3 yds * 4 yds * 6 yds = 440 cubic yards55 ft * 12 ft * 18 ft = 55/3 yds * 4 yds * 6 yds = 440 cubic yards

1 yd = 3 ft 2 yds = 6 ft 3 yds = 9 ft 4 yds = 12 ft . . . 10 yds = 30 ft

1 yd = 3 ft 6 yds * (3 ft/yd) = 18 ft

1 ft = 12 in ⇒ 6in = 6 ÷ 12 ft = 1/2 ft. 1 yd = 3 ft ⇒ 181/2 ft = 181/2 ÷ 3 yds = 61/6 yds

18 ft = 6 yds 12 ft = 4 yds 6 yds x 4 yds = 24 yds2

6 sq. yds

1 yd = 3 ft 2 yds = 6 ft 8 ft is more than that.

12 ft * 18 ft = 4 yds * 6 yds = 24 sq yds

18 feet = 6 yards because there are 3 feet in a yard therefore 18/3 = 6

6 yds., 6 in.

2 yds = 6 ft 7 ft * 6 ft = 42 ft2

There are 3 feet in one yard, so 6 feet is equal to 2 yards.